An Analysis Les Séquestrés D'Altona - Grilli, Anthony Rocco (My University, 1971)
The aim of this study has been to analyse the play Les Séquestrés d'Altona and to situate it in the context of Sartre's though with specific reference to Critique de la Raison Dialectique.
Keywords: Other Languages, Societies, and Cultures; Other Languages, Societies, and Cultures